Nursing Services in the ICU Room: A Scoping Review - Kurniasih, Kurniasih; Rachmawaty, Rini; Hariati, Suni (International Journal Papier Advance and Scientific Review, 2023)
The purpose of this study was to identify nursing services in the ICU. This research method uses a Scoping Review design, using four databases namely PubMed, ScienceDirect, Wiley Online Library, and Eric using keywords based on the PCC method (Population, Concept, Context). The results of the scoping review are all articles explaining that the implementation of nursing services in the ICU room, namely the importance of nursing education, experienced nurses, increasing nursing resources, the importance of monitoring vital signs of critical patients in the ICU room, and communicating well to patients and families in the ICU room to improve the quality of nursing services in the ICU room are the implications of our findings. Conclusion: Our review is the first to explore ICU nursing care in a world country setting. Our findings show that the research sample is nurses working in the ICU rooms of hospitals around the world. Further research is recommended to enhance and facilitate monitoring to further improve patient safety.